Accounting Restatements and Corporate Cash Policy. (April 2020) - Chen, Huili; Chen, Zhihong; Dhaliwal, Dan S.; Huang, Yuan
Using a difference-in-differences approach, we find that the cash holdings of firms increase significantly after announcements of irregularity-related restatements. The increase is larger for firms with a higher demand for precautionary savings and is smaller for firms with less pronounced increase in shareholder control after the restatements. Investments and repurchases of irregularity firms become more sensitive to excess cash after the restatements. In addition, we find that the market value of cash holdings increases after restatements. Overall, the evidence suggests that strengthened shareholder control reduces cash holdings, but this effect is weaker than the increase in cash holdings due to exacerbated precautionary savings concerns. Our study contributes to the literature on the effect of financial reporting credibility on real corporate decisions.